2019
DOI: 10.1186/s12985-019-1158-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-35 modulates the balance between viral specific CD4+CD25+CD127dim/- regulatory T cells and T helper 17 cells in chronic hepatitis B virus infection

Abstract: Background Interleukin (IL)-35 regulates imbalance between regulatory T cells (Tregs) and T helper (Th) 17 cells, leading to an important modulator in autoimmune disorder, cancer, and infectious diseases. Our previous study revealed an immunosuppressive activity of IL-35 in chronic hepatitis B virus (HBV) infection. Thus, the aim of the current study was to investigate the role of regulatory function of IL-35 to viral specific Tregs/Th17 cells balance in chronic HBV infection. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…At the same time, studies found that Tregs and other cell types (including activated myeloid, endothelial cells, regulatory B cells) was capable to secret IL-35 ( Yang et al, 2020a ). Evidence showed that HBV could initiate CD4+ CD25+ Tregs to express IL-35 ( Schneider et al, 2018 ; Yang et al, 2019a ). The expression levels of EBI3, p35 and receptor of IL-35 were also highly expressed in CD4+ CD25+ Tregs of CHB patients.…”
Section: The Roles Of Interleukin-35 In Liver Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, studies found that Tregs and other cell types (including activated myeloid, endothelial cells, regulatory B cells) was capable to secret IL-35 ( Yang et al, 2020a ). Evidence showed that HBV could initiate CD4+ CD25+ Tregs to express IL-35 ( Schneider et al, 2018 ; Yang et al, 2019a ). The expression levels of EBI3, p35 and receptor of IL-35 were also highly expressed in CD4+ CD25+ Tregs of CHB patients.…”
Section: The Roles Of Interleukin-35 In Liver Diseasesmentioning
confidence: 99%
“…The expression levels of EBI3, p35 and receptor of IL-35 were also highly expressed in CD4+ CD25+ Tregs of CHB patients. Notably, their expression levels were proved to be equal in activated and inactivated CD4+ CD25+ Tregs, which suggested that IL-35 could be secreted in activated and inactivated CD4+ CD25+ Tregs ( Yang et al, 2019a ). Additionally, the regulatory function of Tregs in EBI3−/− or p35 −/− mice was significantly inhibited compared to that of control group, implicating that IL-35 was vital for the activity of Treg’ functions.…”
Section: The Roles Of Interleukin-35 In Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…An imbalance in T H 17/T Reg cells was thereby an independent predictive factor for decompensated liver cirrhosis ( Lan et al, 2019 ). In addition, Yang et al demonstrated that IL-35 is responsible to balance the T Reg and T H 17 balance in acute and chronic HBV infection by preferentially increasing virus-specific T Reg cells and the prevention of T H 17 cell differentiation ( Yang et al, 2019 ). In conclusion, T Reg and T H 17 cells contribute to the immune response during viral liver infection and the optimal balance is important for an effective antiviral immune response and prevention of complications ( Figure 4 ).…”
Section: The T H 17/t Reg Cell mentioning
confidence: 99%